2011
DOI: 10.1371/journal.pone.0020589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Schizophrenia Loci by Homozygosity Mapping Using DNA Microarray Analysis

Abstract: The recent development of high-resolution DNA microarrays, in which hundreds of thousands of single nucleotide polymorphisms (SNPs) are genotyped, enables the rapid identification of susceptibility genes for complex diseases. Clusters of these SNPs may show runs of homozygosity (ROHs) that can be analyzed for association with disease. An analysis of patients whose parents were first cousins enables the search for autozygous segments in their offspring. Here, using the Affymetrix® Genome-Wide Human SNP Array 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
3
14
0
1
Order By: Relevance
“…The substantial G component was in accordance with previous studies that indicated the genetic heterogeneity of schizophrenia and the contributions of many rare (possibly dominant) variants in schizophrenia (McClellan et al 2007;Malhotra and Sebat 2012;Gratten et al 2013). Consanguinity induces neuropsychological disorders due to homozygosity (Kurotaki et al 2011), possibly suggesting many recessive genes for the causation of schizophrenia. From the posterior distributions of latent variables, the multiple-hit model with a majority of dominant genes, similar to the previous two-hit model (Girirajan et al 2010), was the most likely explanation for the gene-gene interaction component of schizophrenia presentation.…”
Section: Discussionsupporting
confidence: 90%
“…The substantial G component was in accordance with previous studies that indicated the genetic heterogeneity of schizophrenia and the contributions of many rare (possibly dominant) variants in schizophrenia (McClellan et al 2007;Malhotra and Sebat 2012;Gratten et al 2013). Consanguinity induces neuropsychological disorders due to homozygosity (Kurotaki et al 2011), possibly suggesting many recessive genes for the causation of schizophrenia. From the posterior distributions of latent variables, the multiple-hit model with a majority of dominant genes, similar to the previous two-hit model (Girirajan et al 2010), was the most likely explanation for the gene-gene interaction component of schizophrenia presentation.…”
Section: Discussionsupporting
confidence: 90%
“…The genome-wide ROH overlap pattern was detected using in-house Ruby script (available on request) (44).…”
Section: Methodsmentioning
confidence: 99%
“…HINT1 levels are increased in dorsolateral prefrontal cortex of patients with major depression disorder (Martins-de-Souza et al , 2012) and, adversely, decreased in the same brain regions of patients with schizophrenia (Varadarajulu et al , 2012). Furthermore, association studies reveal HINT1 as a susceptibility gene for schizophrenia (Chen et al , 2008; Kurotaki et al , 2011), bipolar disorder (Elashoff et al , 2007) and nicotine dependence (Jackson et al , 2011; Fang et al , 2014). So far, CMT patients carrying HINT1 mutations have not been neuropsychiatrically evaluated.…”
Section: Introductionmentioning
confidence: 99%